Prediction of Groundwater Level In District Level By Implementing Machine Learning And Advanced Softcomputing Techniques - Devi, Mooramreddy Sree; Rahamathulla, Vempalli (International Journal of Computer Sciences and Engineering, 2025)
Groundwater plays a major role in human life. Now-a-days, the Groundwater levels are gradually decreasing due to pollution and over usage of water and lack of rains. The air pollution caused by industries and human wastage reducess the Groundwater. The increased Groundwater threat is a threat to human life. There is no proper planning and infrastructure to preserve the Groundwater. The bore wells and tube wells pump the Groundwater from a very deep source. Over usage of sand also causes the decrement of Groundwater level. Now-a-days, due to the the scarcity of Groundwater, the farmer is unable to decide the kind crop to be grown in his/her land. This is a complex task. The food bowl of India is day by day becoming weak due to a the scarcity of Groundwater. “Atmospherical science is the best source of study for analyzing and predicting the weather phenomenon and suggests ways and means overcome the problem”[1].